Thomas Flanagan on the Stand: Revisiting Métis Land Claims and the Lists of Rights in Manitoba - O’Toole, Darren (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2010)
AbstractMore than a century after the adoption of section 31 of the Manitoba Act, 1870, which granted 1.4 million acres to the Métis of Manitoba, the descendants were unable to convince a trial judge that the federal and provincial governments improperly implemented this section. In his decision, Judge MacInnes seems to have relied heavily on the historical interpretation of the Crown’s expert witness, political scientist Thomas Flanagan. In this article, the author re-examines the historical evidence concerning the genesis rather than the implementation of s. 31 and finds that, contrary to what Flanagan has asserted, the Métis did indeed make land claims during the Resistance of 1869-70 and mandated their delegate, the abbot Noël-Joseph Ritchot, to negotiate a territorial enclave as consideration for the surrender of their derivative Indian title.